Perovskite solar cell and preparation method thereof
By using guanidine-containing additives as passivating agents in perovskite solar cells, modifying the surface defects under the perovskite absorbing layer and optimizing the interface between the perovskite absorbing layer and the charge transport layer, the interface caused by interface defects is solved. The problem of reducing open circuit voltage improves the efficiency and stability of perovskite solar cells.
Patent Information
- Application Number
- CN202411353178.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
There is a non-ideal charge transfer at the interface between the perovskite absorbing layer and the charge transporting layer in existing perovskite solar cells, resulting in a decrease in the open circuit voltage.
Using guanidine-containing additives as passivating agents to modify the surface defects of the perovskite absorbing layer, and optimize the interface between the perovskite absorbing layer and the charge transport layer through the laminated structure, including hole transport layer and self-assembled single molecule Design of layer, passivation layer, perovskite absorbing layer, charge transport layer and hole barrier layer.
It effectively reduces the interfacial defect density, improves the quality of the perovskite light absorbing layer, reduces the non-radiative recombination of charge, and improves the open circuit voltage and efficiency of perovskite solar cells.
Smart Images

Figure CN119212415A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells, as the third generation of thin-film solar cells, have received widespread attention. In the past decade, their cell efficiency has rapidly increased from 3.8% to 26%. Inverse perovskite solar cells are widely used in the industry due to their good stability and low-temperature preparation process.
[0003] The interface between the perovskite light absorption layer and the charge transport layer is involved in various processes, including carrier separation, transportation, collection and recombination. The interface between the existing perovskite light absorption layer and the charge transport layer has non-ideal charge transfer, resulting in interface defects, which can capture free carriers and convert excited state energy into heat energy, ultimately resulting in a decrease in open circuit voltage (Voc); therefore, how to overcome the above-mentioned technical problems and defects has become a key issue that needs to be solved. Summary of the invention
[0004] In view of the problem that interface defects between the existing perovskite light absorbing layer and the charge transport layer may lead to a decrease in open circuit voltage, the present invention provides a perovskite solar cell and a preparation method thereof.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows: On one hand, the present invention provides a perovskite solar cell, comprising a hole transport layer, a self-assembled monolayer, a passivation layer, a perovskite light absorption layer, a charge transport layer and a hole blocking layer stacked in sequence; the passivation layer contains a guanidine-containing additive.
[0006] Optionally, the guanidine-containing additive includes one or more of 4-guanidinobenzoic acid hydrochloride, 4-nitrophenyl 4-guanidinobenzoate hydrochloride, 4-guanidinobutyric acid, 1-(4-cyanophenyl)guanidine, and 1,3-diphenylguanidine sulfate.
[0007] Optionally, it also includes a substrate electrode layer, which is located on the side of the hole transport layer away from the self-assembled monolayer, and the substrate electrode of the substrate electrode layer is conductive glass, which includes one of ITO conductive glass and FTO conductive glass.
[0008] Optionally, the hole transport layer is NiO; and / or The self-assembled monolayer includes SAM molecules, and the SAM molecules include at least one of Me-4PACz, 2PACz, MeO-2PACz, and 4PADCB.
[0009] Optionally, the perovskite light-absorbing layer includes a perovskite material, the chemical formula of the perovskite material is ABX3, wherein A is at least one of methylamine ion, formamidine ion, and cesium ion; B is at least one of lead (Pb) ion and tin (Sn) ion; X is at least one of halogen ions, including but not limited to at least one of iodine ion and bromide ion; and / or The charge transport layer comprises one of a fullerene material, a metal compound or a fluoride; and / or The hole blocking layer includes an organic tin source, and the organic tin source includes one or more of tetrabutyltin, tetraphenyltin, butylstannic acid, dipropyltin chloride, dimethyltin dichloride, tributyltin chloride, triphenyltin chloride, dibutyltin oxide, and tributyltin oxide.
[0010] Optionally, a metal electrode layer is further included, wherein the metal electrode layer is located on a side of the hole blocking layer away from the charge transport layer, and the metal electrode layer includes a metal electrode, and the metal electrode includes one of copper, silver, gold, platinum, molybdenum or tungsten.
[0011] Another aspect of the present invention provides a method for preparing a perovskite solar cell, comprising the following steps: Step 1, obtaining a precursor, wherein the precursor comprises a stacked hole transport layer and a self-assembled monolayer; Step 2: preparing a guanidine amino acid compound into a guanidine amino acid solution, coating the guanidine amino acid solution on the self-assembled monolayer, and drying to remove the solvent to obtain a passivation layer; Step 3: Continue to prepare the perovskite light absorbing layer, the charge transport layer and the hole blocking layer on the passivation layer.
[0012] Optionally, step 1 includes the following operations: Step 11, placing the conductive glass in a protective atmosphere, sputtering NiO on one side of the conductive glass using a NiO target material using a radio frequency power supply, and forming a hole transport layer on one side of the conductive glass; Step 12: Add SAM molecules to an ethanol solution to prepare a 0.1-1 mg / mL SAM molecule solution. In a vacuum environment, coat 80 μL-120 μL of the SAM molecule solution on the surface of the hole transport layer to obtain a self-assembled monolayer.
[0013] Optionally, step 3 includes the following operations: Step 31: Cs X FA Y MA 1-X-Y PbI Z Prepare a 1-2M perovskite precursor solution, and coat 80 μL-120 μL of the perovskite precursor solution on the passivation layer to obtain a perovskite light-absorbing layer; Step 32, depositing a fullerene material, a metal compound or a fluoride with a thickness of 10-30 nm on the perovskite light-absorbing layer by a vacuum evaporation method to prepare a charge transport layer; Step 33, depositing an organic tin source with a thickness of 10-20 nm on the upper surface of the charge transport layer to prepare a hole blocking layer; Step 34: depositing a metal electrode with a thickness of 70-130 nm on the hole blocking layer by vacuum evaporation to prepare a perovskite solar cell.
[0014] Optionally, Cs in step 31 X FA Y MA 1-X-Y PbI Z The preparation method is as follows: CsI, MAI, FAI, and PbI2 are weighed and mixed in a ratio of 18:25.8:222.3:730.7 to form a mixture; the mixture is dissolved in an organic solvent to prepare a perovskite precursor solution; the organic solvent includes N,N-dimethylformamide and dimethyl sulfoxide; the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 4:1.
[0015] According to the perovskite solar cell provided by the present invention, guanidine amino acid is used as a passivator to modify the lower surface defects of the perovskite light absorbing layer and improve the interface defects between the perovskite light absorbing layer and the charge transport layer; the guanidine-containing additive effectively passivates these defects and promotes the growth of grains, thereby obtaining a perovskite light absorbing layer with low defect density and high grain quality; due to the reduction in defect density and the improvement in the quality of the perovskite light absorbing layer film, the non-radiative recombination of charges in the perovskite solar cell is reduced, thereby increasing the open circuit voltage of the perovskite solar cell, and improving the efficiency and stability of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 is a schematic structural diagram of a perovskite solar cell provided by an embodiment of the present invention; Figure 2 Schematic diagram of conversion efficiency of perovskite solar cells in Example 1 of the present invention and Comparative Examples 1-2; Figure 3 Schematic diagram of the filling factor of the perovskite solar cell in Example 1 of the present invention and Comparative Examples 1-2; Figure 4 Schematic diagram of the open circuit voltage of the perovskite solar cell in Example 1 of the present invention and Comparative Examples 1-2; Figure 5 Schematic diagram of short-circuit current density of perovskite solar cells in Example 1 of the present invention and Comparative Examples 1-2; The reference numerals in the drawings of the specification are as follows: 1-substrate electrode layer; 2-hole transport layer; 3-self-assembled monolayer; 4-passivation layer; 5-perovskite light absorption layer; 6-charge transport layer; 7-hole blocking layer; 8-metal electrode layer. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] In the description of the present invention, it should be understood that the terms "longitudinal", "radial", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0020] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0022] like Figure 1-Figure 2As shown, in one embodiment, the present invention provides a perovskite solar cell, comprising a hole transport layer 2, a self-assembled monolayer 3, a passivation layer 4, a perovskite light absorbing layer 5, a charge transport layer 6 and a hole blocking layer 7 stacked in sequence; the passivation layer 4 contains a guanidine-containing additive.
[0023] The interface between the perovskite light absorbing layer 5 and the charge transport layer 6 in a perovskite solar cell is involved in various processes, including carrier separation, transport, collection, and recombination. There are interfacial defects at the interface between the perovskite light absorbing layer 5 and the charge transport layer 6, which can capture free carriers and convert excited state energy into heat energy, ultimately resulting in a decrease in the open circuit voltage (Voc).
[0024] The present invention adopts guanidine amino acid as a passivator to modify the lower surface defects of the perovskite light absorbing layer 5 and improve the interface defects between the perovskite light absorbing layer 5 and the charge transport layer 6; the guanidine-containing additive effectively passivates these defects and promotes the growth of grains, thereby obtaining a perovskite light absorbing layer 5 with low defect density and high grain quality; due to the reduction of defect density and the improvement of the film quality of the perovskite light absorbing layer 5, the non-radiative recombination of charges in the perovskite solar cell is reduced, thereby increasing the open circuit voltage of the perovskite solar cell, and improving the efficiency and stability of the perovskite solar cell.
[0025] In one embodiment, the guanidine-containing additive includes one or more of 4-guanidinobenzoic acid hydrochloride, 4-nitrophenyl 4-guanidinobenzoate hydrochloride, 4-guanidinobutyric acid, 1-(4-cyanophenyl)guanidine, and 1,3-diphenylguanidine sulfate.
[0026] In a preferred embodiment, the guanidine-containing additive is selected from 4-guanidinobenzoic acid hydrochloride; 4-guanidinobenzoic acid hydrochloride is used as a passivating agent to modify the surface defects of the perovskite under the perovskite light absorbing layer 5 and improve the interface between the perovskite and the charge transport layer 6, and promote the growth of grains. Thus, a perovskite light absorbing layer 5 with low defect density and high grain quality is obtained. Due to the reduction of defect density and the improvement of the film quality of the perovskite light absorbing layer 5, the non-radiative recombination of charges is reduced, thereby improving the open circuit voltage of the device.
[0027] In one embodiment, the perovskite solar cell also includes a base electrode layer 1, which is located on the side of the hole transport layer 2 away from the self-assembled monolayer 3, and the base electrode of the base electrode layer 1 is conductive glass, and the conductive glass includes one of ITO conductive glass or FTO conductive glass.
[0028] Specifically, the base electrode of the base electrode layer 1 may also be a transparent flexible conductive material, and the transparent conductive flexible material is one of indium tin oxide polyethylene naphthalate and indium tin oxide polyethylene terephthalate.
[0029] In one embodiment, the hole transport layer 2 is NiO.
[0030] Specifically, by forming the hole transport layer 2 on the surface of the base electrode layer 1, the NiO compound has a higher hole mobility, thereby achieving the technical effect of efficiently transporting holes.
[0031] In one embodiment, the self-assembled monolayer 3 includes SAM molecules, and the SAM molecules include at least one of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) and [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid (4PADCB).
[0032] In a preferred embodiment, the SAM molecule is selected from Me-4PACz, and Me-4PACz is used to form a self-assembled monolayer 3 on the surface of the hole transport layer 2, thereby achieving a hole transport effect of passivating the hole transport layer.
[0033] In one embodiment, the perovskite light absorbing layer includes a perovskite material, and the chemical formula of the perovskite material is ABX3, wherein A is at least one of methylamine ion, formamidine ion, and cesium ion, B is at least one of lead ion and tin ion, and X is at least one of halogen ions, including but not limited to at least one of iodine ion and bromide ion.
[0034] In a preferred embodiment, the perovskite light absorbing layer includes Cs 0.05 FA 0.85 MA 0.1 PbI3, using Cs 0.05 FA 0.85 MA 0.1 PbI3, as the main material of the perovskite light absorption layer, can achieve the effect of generating electrons and holes through the photovoltaic effect under light.
[0035] In one embodiment, the charge transport layer 6 includes one of fullerene materials, metal compounds or fluorides.
[0036] Specifically, the fullerene material is fullerene or a fullerene derivative, the fullerene material is preferably C60, the fullerene derivative is preferably PCBM, the metal compound is a metal oxide or a metal-doped oxide, the metal type is Zn, Pb, Mo, Al, Ni, Sn or Mg; the fluoride is LiF or CaF2; By using one of fullerene materials, metal compounds or fluorides as the main material of the charge transport layer 6, there is an effect of transporting electrons and blocking the transport of holes.
[0037] In one embodiment, the hole blocking layer 7 includes an organic tin source, and the organic tin source includes one or more of tetrabutyltin, tetraphenyltin, butylstannic acid, dipropyltin chloride, dimethyltin dichloride, tributyltin chloride, triphenyltin chloride, dibutyltin oxide, and tributyltin oxide.
[0038] In one embodiment, the perovskite solar cell further includes a metal electrode layer 8, which is located on the side of the hole blocking layer 7 away from the charge transport layer 6, and the metal electrode layer 8 includes a metal electrode, and the metal electrode includes one of copper, silver, gold, platinum, molybdenum or tungsten.
[0039] The metal electrode layer 8 is a metal electrode commonly used in perovskite solar cells in the prior art, and is mainly a metal with high electrical conductivity, mainly including at least one of copper, silver, gold, platinum, molybdenum and tungsten. Using at least one of copper, silver, gold, platinum, molybdenum and tungsten as a metal electrode has the effect of transferring charges.
[0040] Another aspect of the present invention provides a method for preparing a perovskite solar cell, comprising the following steps: Step 1, obtaining a precursor, wherein the precursor includes a stacked hole transport layer and a self-assembled monolayer; Step 2: preparing a guanidine amino acid compound into a guanidine amino acid solution, coating the guanidine amino acid solution on the self-assembled monolayer, and drying to remove the solvent to obtain a passivation layer; Step 3: Continue to prepare the perovskite light absorbing layer, the charge transport layer and the hole blocking layer on the passivation layer.
[0041] In one embodiment, step 1 includes the following operations: Step 11: Place the conductive glass in a protective atmosphere and use a radio frequency power source to sputter NiO on one side of the conductive glass. , forming a hole transport layer 2 on one side of the conductive glass; Step 12: Add SAM molecules to an ethanol solution to prepare a 0.1-1 mg / mL SAM molecule solution, and coat 80 μL-120 μL of the SAM molecule solution on the surface of the hole transport layer 2 under a vacuum environment to obtain a self-assembled monolayer 3 .
[0042] Specifically, in step 11, the conductive glass is transferred to a magnetron sputtering chamber, a NiO target is fixed on the sputtering target position, the chamber is closed, and NiO is sputtered on one side of the conductive glass using a radio frequency power supply. , A hole transport layer 2 is formed on one side of the conductive glass.
[0043] In step 12, the conductive glass with the hole transport layer 2 is transferred to a nitrogen glove box, 80 μL-120 μL of the SAM molecular solution is dripped on the surface of the hole transport layer 2, and then a self-assembled monolayer 3 is formed on the surface of the hole transport layer 2 by spin coating, scraper coating, spray coating, screen printing, etc.; Specifically, the volume of the SAM molecular solution added to the surface of the hole transport layer 2 is: any point value among 80μL, 85μL, 90μL, 95μL, 100μL, 105μL, 110μL, 115μL or 120μL, or a range value consisting of any two point values; in a preferred embodiment, the volume of the SAM molecular solution added to the surface of the hole transport layer 2 is 90-110μL; more preferably, the volume of the SAM molecular solution added to the surface of the hole transport layer 2 is 100μL.
[0044] In one embodiment, the sputtering power in step 11 is RF-500W, the protective atmosphere is argon, the sputtering pressure is 0.2-0.5 Pa, and the sputtering time is 15-25 min.
[0045] Specifically, the sputtering gas pressure is any point value among 0.2Pa, 0.3Pa, 0.4Pa or 0.5Pa, or a range value consisting of any two point values; in a preferred embodiment, the sputtering gas pressure is 0.3Pa.
[0046] Specifically, the sputtering time is any point value among 15min, 16min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min or 25min, or a range value consisting of any two point values; in a preferred embodiment, the sputtering time is 20min.
[0047] In one embodiment, in step 12, after coating the SAM molecule solution, the conductive glass needs to be placed on a hot stage and annealed at a temperature of 80-120° C. for 8-12 minutes; Specifically, after coating the SAM molecular solution, the annealing temperature of the conductive glass is any point value among 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, or a range value consisting of any two point values; in a preferred embodiment, after coating the SAM molecular solution, the annealing temperature of the conductive glass is 100°C.
[0048] Specifically, after coating the SAM molecular solution, the annealing time of the conductive glass is any point value among 8min, 9min, 10min, 11min or 22min, or a range value consisting of any two point values; in a preferred embodiment, after coating the SAM molecular solution, the annealing time of the conductive glass is 10min.
[0049] In one embodiment, step 2 includes the following operations: A guanidine amino acid compound is added to an isopropanol solution to prepare a 0.2 mg / mL-5 mg / mL guanidine amino acid solution, and 80 μL-120 μL of the guanidine amino acid solution is coated on the self-assembled monolayer 3 to obtain a passivation layer 4.
[0050] In step 2, 80 μL-120 μL of guanidine amino acid solution is dripped onto the surface of the self-assembled monolayer 3, and then a passivation layer 4 is formed on the surface of the self-assembled monolayer 3 by spin coating, scraper coating, spray coating, screen printing, etc.; Specifically, the volume of the guanidine amino acid solution added to the surface of the self-assembled monolayer 3 is: any point value among 80μL, 85μL, 90μL, 95μL, 100μL, 105μL, 110μL, 115μL or 120μL, or a range value consisting of any two point values; in a preferred embodiment, the volume of the guanidine amino acid solution added to the surface of the self-assembled monolayer 3 is 90-110μL; more preferably, the volume of the guanidine amino acid solution added to the surface of the self-assembled monolayer 3 is 100μL.
[0051] In step 2, after coating the guanidine amino acid solution, the conductive glass needs to be placed on a hot plate and annealed at 80-120° C. for 8-12 minutes; Specifically, after coating the guanidine amino acid solution, the annealing temperature of the conductive glass is any point value of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, or a range value consisting of any two point values; in a preferred embodiment, after coating the guanidine amino acid solution, the annealing temperature of the conductive glass is 100°C.
[0052] Specifically, after coating the guanidine amino acid solution, the annealing time of the conductive glass is any point value among 8min, 9min, 10min, 11min or 22min, or a range value consisting of any two point values; in a preferred embodiment, after coating the guanidine amino acid solution, the annealing time of the conductive glass is 10min.
[0053] In one embodiment, step 3 includes the following operations: Step 31: Cs X FA Y MA 1-X-Y PbI Z A 1-2M perovskite precursor solution is prepared, and 80 μL-120 μL of the perovskite precursor solution is coated on the passivation layer 4 to obtain a perovskite light absorbing layer 5; Step 32: depositing a fullerene material, a metal compound or a fluoride with a thickness of 10-30 nm on the perovskite light absorbing layer 5 by vacuum evaporation to prepare a charge transport layer 6; Step 33, depositing an organic tin source with a thickness of 10-20 nm on the upper surface of the charge transport layer 6 to prepare a hole blocking layer 7; Step 34: deposit a metal electrode with a thickness of 70-130 nm on the hole blocking layer 7 by vacuum evaporation to prepare a perovskite solar cell.
[0054] In step 31, the concentration of the perovskite precursor solution is any point value among 1M, 1.08M, 1.17M, 1.25M, 1.33M, 1.41M, 1.49M, 1.55M, 1.67M, 1.75M, 1.83M, 1.92M or 2M, or a range value consisting of any two point values; in a preferred embodiment, the concentration of the perovskite precursor solution is 1.49M-1.83M; more preferably, the concentration of the perovskite precursor solution is 1.67M.
[0055] 80 μL-120 μL of the perovskite precursor solution is dripped onto the surface of the passivation layer 4, and then a perovskite light absorbing layer 5 is formed on the surface of the passivation layer 4 by spin coating, scraper coating, spray coating, screen printing or the like; Specifically, the volume of the perovskite precursor solution added to the surface of the passivation layer 4 is: any point value among 80μL, 85μL, 90μL, 95μL, 100μL, 105μL, 110μL, 115μL or 120μL, or a range value composed of any two point values; in a preferred embodiment, the volume of the perovskite precursor solution added to the surface of the passivation layer 4 is 90-110μL; more preferably, the volume of the perovskite precursor solution added to the surface of the passivation layer 4 is 100μL.
[0056] In step 31, after coating the perovskite precursor solution, the conductive glass needs to be placed on a hot plate and annealed at a temperature of 90-130°C for 15-25 minutes.
[0057] Specifically, after coating the perovskite precursor solution, the annealing temperature of the conductive glass is any point value among 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, or a range value consisting of any two point values; in a preferred embodiment, after coating the perovskite precursor solution, the annealing temperature of the conductive glass is 110°C.
[0058] Specifically, after coating the perovskite precursor solution, the annealing time of the conductive glass is any point value among 15min, 16min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min or 25min, or a range value consisting of any two point values; in a preferred embodiment, after coating the perovskite precursor solution, the annealing time of the conductive glass is 20min.
[0059] In one embodiment, Cs in step 31 X FA Y MA 1-X-Y PbI Z The preparation method is as follows: CsI, MAI, FAI, and PbI2 are weighed and mixed in a ratio of 18:25.8:222.3:730.7 to form a mixture; the mixture is dissolved in an organic solvent to prepare a perovskite precursor solution; the organic solvent includes N,N-dimethylformamide and dimethyl sulfoxide; the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 4:1.
[0060] In step 32, the conductive glass having the perovskite light absorbing layer 5 is placed in a vacuum evaporator; a perovskite precursor solution is deposited on the surface of the passivation layer 4 by vacuum evaporation; Specifically, the thickness of the electron transport layer is: any point value among 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm, 26nm, 28nm or 30nm, or a range value consisting of any two point values; in a preferred embodiment, the thickness of the electron transport layer is 16nm-24nm; more preferably, the thickness of the electron transport layer is 20nm.
[0061] In one embodiment, in step 32, the vacuum degree of the vacuum evaporator is P1Pa, and the value range of P1 is: P1<10 - 4 Pa, deposition rate 0.1-1Å·S -1 ; When the deposition rate is 0.1-1Å·S -1 When the electron transport layer is formed, the consistency of the electron transport layer is ensured.
[0062] In step 33, the conductive glass with the electron transport layer is placed in a space-type ALD deposition device, and an organic tin source is deposited on the surface of the electron transport layer to form a hole blocking layer 7; Specifically, the deposition thickness of the organic tin source is: any point value among 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, or a range value consisting of any two point values; in a preferred embodiment, the deposition thickness of the organic tin source is 12nm-18nm; more preferably, the deposition thickness of the organic tin source is 15nm.
[0063] In step 33, the deposition temperature of the organotin source is 100-250°C, and the heating temperature of the organotin source bottle is 30-50°C; Furthermore, the carrier plate in the deposition device has a swing time of 100 mm / s and a cycle of 60 times.
[0064] In step 34 , the conductive glass having the hole blocking layer 7 is placed in the vacuum evaporator again; a metal electrode is deposited on the surface of the hole blocking layer 7 by vacuum evaporation to form a metal electrode layer 8 .
[0065] Specifically, the thickness of the metal electrode layer 8 is: any point value among 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 125nm or 130nm, or a range value consisting of any two point values; in a preferred embodiment, the thickness of the metal electrode layer 8 is 90nm-110nm; more preferably, the thickness of the metal electrode layer 8 is 100nm.
[0066] In step 34, the vacuum degree of the vacuum evaporator is P2Pa, and the value range of P2 is: P2<10 -4 Pa, deposition rate 0.1-1Å·S -1 .
[0067] When the deposition rate is 0.1-1Å·S -1 When doing so, ensure the consistency of the metal electrode layer.
[0068] In one embodiment, before using the conductive glass in step 11, the conductive glass is firstly ultrasonically cleaned with an ethanol solution for 15-30 minutes, then dried in an oven at 70-90° C., and finally treated with UV ozone for 15-30 minutes.
[0069] Specifically, the time for ultrasonically cleaning the conductive glass using an ethanol solution is any point value among 15min, 16min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min, 25min, 26min, 27min, 28min, 29min or 30min, or a range value consisting of any two point values; in a preferred embodiment, the time for ultrasonically cleaning the conductive glass using an ethanol solution is 20min.
[0070] Specifically, the temperature for drying the conductive glass in an oven is any point value among 70°C, 75°C, 80°C, 85°C or 90°C, or a range value consisting of any two point values; in a preferred embodiment, the temperature for drying the conductive glass in an oven is 80°C.
[0071] Specifically, the time for treating the conductive glass with UV ozone is any point value among 15min, 16min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min, 25min, 26min, 27min, 28min, 29min or 30min, or a range value consisting of any two point values; in a preferred embodiment, the time for treating the conductive glass with UV ozone is 20min.
[0072] The preparation method and application of the present invention will be further described in detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0073] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0074] Example 1 A perovskite solar cell comprises a base electrode layer, a hole transport layer, a self-assembled monolayer, a passivation layer, a perovskite light absorption layer, a charge transport layer, a hole blocking layer and a metal electrode layer stacked in sequence; A method for preparing a perovskite solar cell, the specific steps of the method are as follows: The ITO conductive glass was ultrasonically cleaned with ethanol for 20 min, dried in an oven at 80°C, and treated with UV ozone for 20 min; Transfer the UV ozone treated ITO conductive glass to the magnetron sputtering chamber; fix the NiO target on the sputtering target position, close the chamber, use the RF power supply to sputter NiO, adjust the sputtering power RF-500W, pure argon (Ar) sputtering atmosphere, process gas pressure 0.2-0.5Pa, sputtering time 15-25min, and take it out after sputtering; Me-4PACz was added to an ethanol solution to prepare a 0.5 mg / mL SAM solution. The ITO conductive glass with a hole transport layer was moved to a nitrogen glove box. 100 μL of 0.5 mg / mL SAM solution was added to the hole transport layer for spin coating, and then placed on a hot stage for annealing at 100°C for 10 min to obtain a self-assembled monolayer. GBAC was added to an isopropanol solution to prepare a 1 mg / mL GBAC solution, 100 μL of the 1 mg / mL GBAC solution was dropped onto the self-assembled monolayer and spin-coated, and then placed on a hot stage for annealing at 100°C for 10 min to obtain a passivation layer; 1.65 mg CsI, 26.5 mg MAI, 243.6 mg FAI, 807.22 mg PbI2, and 16.67 mg MACl were added to 800 μl DMF and 200 μl DMSO solution to prepare 1.67 M CsI. 0.05 FA 0.85 MA 0.1 PbI3 precursor solution; 100ul of the perovskite precursor solution was spin-coated onto the passivation layer, and then placed on a hot plate and annealed at 110°C in a glove box for 20 minutes to obtain a perovskite light-absorbing layer; Transfer the device prepared in step 5 to a vacuum evaporator and evaporate C60 as an electron transport layer. The vacuum degree of the vacuum evaporator is recommended to be less than 10 -4 Pa, deposition rate 0.1-1Å·S -1 , the deposition thickness is 20nm, and an electron transport layer is obtained; The device prepared in step 6 was transferred to a spatial ALD deposition device. The organic tin source was tetrakis(dimethylamino)tin (TDMASn). The deposition temperature was set to 150°C. The heating temperature of the organic tin source bottle was 30-50°C. The carrier swing time was 100 mm / s, the cycle was 60 times, the deposition thickness was 15 nm, and the hole blocking layer 7 and the metal electrode layer were obtained. The device prepared in step 7 is transferred to a vacuum deposition chamber to deposit silver electrodes; the vacuum degree during the vacuum deposition process is less than 10 -4 Pa, deposition rate 0.1-1Å·S -1 , the deposition thickness is 100nm, and a metal electrode layer is obtained.
[0075] Comparative Example 1 Comparative Example 1 is used to illustrate a perovskite solar cell without a passivation layer disclosed in the present invention, and includes most of the operating steps in Example 1, except that step (4) is removed based on Example 1.
[0076] Comparative Example 2 Comparative Example 2 is used to illustrate a perovskite solar cell without a passivation layer disclosed in the present invention, which includes most of the operating steps in Example 1, except that step (4) is removed from Example 1, and the preparation process of step (5) is as follows: 1.65 mg CsI, 26.5 mg MAI, 243.6 mg FAI, 807.22 mg PbI2, and 16.67 mg MACl were added to 800 μl DMF and 200 μl DMSO solution to prepare 1.67 M CsI. 0.05 FA 0.85 MA 0.1 PbI3 precursor solution; in Cs 0.05 FA 0.85 MA 0.1 1 mg / ml GBAC solution was added to the PbI3 precursor solution to form a perovskite precursor solution. 100 ul of the perovskite precursor solution was spin-coated onto the passivation layer, and then placed on a hot plate and annealed at 110 °C in a glove box for 20 minutes to obtain a perovskite light-absorbing layer. The following performance tests were performed on the perovskite solar cells prepared in Example 1, Comparative Example 1 and Comparative Example 2; Photoelectric conversion efficiency, fill factor, short-circuit current, open-circuit voltage test: The efficiency of perovskite solar cell devices was tested using an AM1.5G solar simulator (Enlitech, SS-F5-3A, Enlitech Technology Co., Ltd.), which included a calibration silicon cell (Enlitech, SRC-2000, Enlitech Technology Co., Ltd.) and a source meter tester (KEITHLEY2400, Tektronix LLC). Test method: Use an AM1.5G solar simulator to test the efficiency of perovskite solar cell devices. First, use a standard silicon cell to calibrate to the light intensity of 1 sun, and then apply a scan voltage to the perovskite solar cell device through a source meter. The scan voltage range is -0.1V to 1.2V, the scan rate is 0.1V / s, and the perovskite solar cell area is 0.0735cm 2 ; The test results are shown in Table 1: Table 1 Test results of Example 1 of the present invention and Comparative Examples 1-2 The photoelectric conversion efficiency of the perovskite solar cells prepared by comparing Example 1, Comparative Example 1 and Comparative Example 2 is as follows: Figure 2-5 As shown, Example 1 uses 4-guanidinobenzoic acid hydrochloride as a passivating agent to modify the lower surface defects of the perovskite light absorbing layer and improve the interface defects between the perovskite light absorbing layer and the charge transport layer, thereby extending the carrier lifetime and reducing the occurrence of non-radiative recombination at the buried interface; thereby improving the open circuit voltage of the perovskite solar cell, and the photoelectric conversion efficiency of the perovskite solar cell is 23.07%, which is higher than that of the solar cell prepared in Comparative Example 1 without using a guanidino-containing additive as a passivation layer; and is also higher than that of the solar cell prepared in Comparative Example 2 by directly adding a guanidino-containing additive to the perovskite light absorbing layer; At the same time, the guanidine ions in the guanidine-containing additives optimize the band alignment of the lower surface of the perovskite light-absorbing layer and the interface between the perovskite light-absorbing layer and the charge transport layer, thereby accelerating the charge extraction and transfer at the perovskite light-absorbing layer. The passivation of the perovskite light-absorbing layer and the charge transport layer and the modulation of the interface band alignment increase the average open-circuit voltage of the device by 20mV, the short-circuit current by 0.23A, and the fill factor by about 3%.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A perovskite solar cell, characterized in that: The invention comprises a hole transport layer, a self-assembled monomolecular layer, a passivation layer, a perovskite light absorption layer, a charge transport layer and a hole blocking layer which are stacked in sequence; the passivation layer comprises a guanidine-containing additive.
2. The perovskite solar cell according to claim 1, characterized in that: The guanidine-containing additives include one or more of 4-guanidinobenzoic acid hydrochloride, 4-nitrophenyl 4-guanidinobenzoate hydrochloride, 4-guanidinobutyric acid, 1-(4-cyanophenyl)guanidine, and 1,3-diphenylguanidine sulfate.
3. The perovskite solar cell according to claim 1, characterized in that: It also includes a substrate electrode layer, which is located on the side of the hole transport layer away from the self-assembled monolayer. The substrate electrode of the substrate electrode layer is conductive glass, and the conductive glass includes one of ITO conductive glass and FTO conductive glass.
4. The perovskite solar cell according to claim 1, characterized in that: The hole transport layer is NiO; and / or The self-assembled monolayer includes SAM molecules, and the SAM molecules include at least one of Me-4PACz, 2PACz, MeO-2PACz, and 4PADCB.
5. The perovskite solar cell according to claim 1, characterized in that: The perovskite light-absorbing layer comprises a perovskite material, the chemical formula of the perovskite material is ABX3, wherein A is at least one of methylamine ion, formamidine ion, and cesium ion, B is at least one of lead ion and tin ion, and X is at least one of halogen ions, including but not limited to at least one of iodide ion and bromide ion; and / or The charge transport layer comprises one of a fullerene material, a metal compound or a fluoride; and / or The hole blocking layer includes an organic tin source, and the organic tin source includes one or more of tetrabutyltin, tetraphenyltin, butylstannic acid, dipropyltin chloride, dimethyltin dichloride, tributyltin chloride, triphenyltin chloride, dibutyltin oxide, and tributyltin oxide.
6. The perovskite solar cell according to claim 1, characterized in that: It also includes a metal electrode layer, which is located on the side of the hole blocking layer away from the charge transport layer. The metal electrode layer includes a metal electrode, and the metal electrode includes one of copper, silver, gold, platinum, molybdenum or tungsten.
7. A method for preparing a perovskite solar cell according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, obtaining a precursor, wherein the precursor comprises a stacked hole transport layer and a self-assembled monolayer; Step 2: preparing a guanidine amino acid compound into a guanidine amino acid solution, coating the guanidine amino acid solution on the self-assembled monolayer, and drying to remove the solvent to obtain a passivation layer; Step 3: Continue to prepare the perovskite light absorbing layer, the charge transport layer and the hole blocking layer on the passivation layer.
8. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The step 1 includes the following operations: Step 11, placing the conductive glass in a protective atmosphere, sputtering NiO on one side of the conductive glass using a NiO target material using a radio frequency power supply, and forming a hole transport layer on one side of the conductive glass; Step 12: Add SAM molecules to an ethanol solution to prepare a 0.1-1 mg / mL SAM molecule solution. In a vacuum environment, coat 80 μL-120 μL of the SAM molecule solution on the surface of the hole transport layer to obtain a self-assembled monolayer.
9. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The step 3 includes the following operations: Step 31: Cs X FA Y MA 1-X-Y PbI Z Prepare a 1-2M perovskite precursor solution, apply 80 μL-120 μL of the perovskite precursor solution on the passivation layer to obtain a perovskite light-absorbing layer; Step 32, depositing a fullerene material, a metal compound or a fluoride with a thickness of 10-30 nm on the perovskite light-absorbing layer by a vacuum evaporation method to prepare a charge transport layer; Step 33, depositing an organic tin source with a thickness of 10-20 nm on the upper surface of the charge transport layer to prepare a hole blocking layer; Step 34: depositing a metal electrode with a thickness of 70-130 nm on the hole blocking layer by vacuum evaporation to prepare a perovskite solar cell.
10. The method for preparing a perovskite solar cell according to claim 9, characterized in that: Cs in step 31 X FA Y MA 1-X-Y PbI Z The preparation method is as follows: CsI, MAI, FAI, and PbI2 are weighed and mixed in a ratio of 18:25.8:222.3:730.7 to form a mixture; the mixture is dissolved in an organic solvent to prepare a perovskite precursor solution; the organic solvent includes N,N-dimethylformamide and dimethyl sulfoxide; the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 4:1.